Microwave-assisted choline chloride/1, 2-propanediol/methyl isobutyl ketone biphasic system for one-pot fractionation and valorization of Eucalyptus biomass. (February 2023) - Sun, Li-Li; Yue, Zhuang; Sun, Shao-Chao; Li, Yu; Cao, Xue-Fei; Sun, Shao-Ni
Graphical abstract: Highlights: A short-time DES/MIBK system was introduced to depolymerize Eucalyptus . Combination with AlCl3 ·6H2 O and HCl was successfully for improving furfural yield. The recovered lignin had a low molecular weight (2040–1380 g/mol). The highest furfural yield (55.4 %) and cellulose yield (90.3 %) were attached. Abstract: The developing of pretreatment method to break the biomass barrier of lignocellulosic is a challenging task for achieve high value utilization. A fast microwave-assisted choline chloride/1, 2-propanediol/methyl isobutyl ketone biphasic system was constructed for pretreating Eucalyptus to the production of furfural and cellulose-rich residues and the extraction of lignin. Results showed that the combination of AlCl3 ·6H2 O and HCl had the best catalytic ability for furfural production among the examined catalysts. Under the optimal conditions (140 °C, 15 min, 0.075 M AlCl3 ·6H2 O, 0.05 M HCl), the furfural yield of 55.4 %, the glucose yield of 90.3 % and the delignification rate of 92.4 % could be achieved. Moreover, the extracted lignin samples with a low polydispersity (1.55–1.73) and molecular weight (1380–2040 g/mol) are promising to act as precursor for the value-add products processing. These findings demonstrated an ultrafast pretreatment process with excellent results in biomass fractionation and comprehensive utilization of biomass components.